Diversity and Evolutionary History of the Symbiontida (Euglenozoa) - Yubuki, Naoji; Leander, Brian S. (Frontiers in Ecology and Evolution, 2018)
Several lineages of euglenozoans are enveloped with epibiotic bacteria and live in low oxygen and anoxic marine sediments, such as Bihospites bacati and Calkinsia aureus. A combination of shared ultrastructural traits and molecular phylogenetic inferences demonstrate that these lineages belong to a clade called the “Symbiontida”. Bihospites and Calkinsia possess all of the synapomorphies for the Euglenozoa plus several novel traits. Bihospites has a distinctive cell surface organization reminiscent of the pellicle strips in euglenids, a robust C-shaped feeding apparatus that encircles the nucleus, and a diverse community of epibiotic bacteria. Calkinsia has a novel “extrusomal pocket” and a thick (orange) extracellular matrix beneath a uniform layer of epibiotic bacteria. Despite the absence of molecular phylogenetic data, similar ultrastructural traits in Postgaardi mariagerensis and its epibiotic bacteria strongly suggest that this species is also a member of the Symbiontida. Molecular phylogenetic trees inferred from small subunit (SSU) ribosomal DNA sequences have shown that Bihospites and Calkinsia group strongly with a diverse set of environmental DNA sequences (eDNA) generated from low-oxygen marine samples collected at different depths from different locations around the world. These data demonstrate a diverse array of symbiontids that have yet to be characterized at the genomic, cellular, and behavior levels, which underscores how poorly we currently understand the biology and ecology of the group. Moreover, current data suggest that the communities of epibiotic bacteria associated with Bihospites, Calkinsia and Postgaardi co-evolved with their hosts and are metabolically integrated with modified mitochondria positioned immediately beneath the host’s plasma membrane. No symbiontid species has ever been cultivated, so improved knowledge about these eukaryotic organisms and their intimate relationships with bacteria in low oxygen environments will likely be achieved using culture-independent approaches, such as isolated-cell metagenomics.